Revisiting the Role of Insulin-Like Growth Factor-I Receptor Stimulating Activity and the Apolipoprotein E in Alzheimer’s Disease - Galle, Sara A.; van der Spek, Ashley; Drent, Madeleine L.; Brugts, Michael P.; Scherder, Erik J. A.; Janssen, Joseph A. M. J. L.; Ikram, M. Arfan; van Duijn, Cornelia M. (Frontiers in Aging Neuroscience, 2019)
Background: Alterations in Insulin-Like Growth Factor I (IGF-I) signaling have been associated with dementia and Alzheimer’s disease. Studies on the association between IGF-I levels and dementia risk have been inconclusive. We reported earlier that higher levels of IGF-I receptor stimulating activity are associated with a higher prevalence and incidence of dementia. Objective: In the present study, we test the robustness of the association between IGF-I receptor stimulating activity and dementia by extending the follow-up period to 16 years and investigate possible effect modification by apolipoprotein E. Methods: At baseline, circulating IGF-I receptor stimulating activity was determined by the IGF-I KIRA assay in 1,014 elderly from the Rotterdam Study. Dementia was assessed from baseline (1997-1999) to follow-up in January 2015. Associations of IGF-I receptor stimulating activity and incident dementia were assessed with Cox proportional hazards models. Results: During 10,752 person-years of follow-up, 174 people developed dementia. In the extended follow-up we no longer observed a dose-response relationship between IGF-I receptor stimulating activity and risk of dementia (adjusted odds ratio 1.11; 95% CI 0.97-1.28). Interestingly, we found evidence of an interaction between ApoE-4 and tertiles of IGF-I receptor stimulating activity. IGF-I receptor stimulating activity in the median and top tertiles was related to increased dementia incidence in hetero- and homozygotes of the ApoE-4 allele, but did not show any association with dementia risk in people without the ApoE-4 allele (adjusted odds ratio medium versus low IGF-I receptor stimulating activity in ApoE-4 carriers: 1.45; 95% CI 1.00-2.12). These findings suggest a threshold effect in ApoE-4 carriers. In line with the hypothesis that downregulation of IGF-I signaling is associated with increased dementia risk, ApoE-4 homozygotes without prevalent dementia displayed lower levels of IGF-I receptor stimulating activity than heterozygotes and non-carriers. Conclusion: The findings shed new light on the association between IGF-I signaling and the neuropathology of dementia and ask for replication in other cohorts, using measures of IGF-I receptor stimulating activity rather than total serum levels as putative markers of dementia risk.